THE INFLUENCE OF THE TAX WAIVER, TAX PENALTIES AND THE E-SAMSAT SYSTEM ON MOTOR VEHICLE TAXPAYER COMPLIANCE - Salma Shafira Nurfadillah; Yati Mulyati (SEAN Institute, 2023)
The purpose of this study was to determine the impact of the tax waiver, tax penalties, the e-samsat system on taxpayer compliance. tax waiver, tax penalties, the E-Samsat system are experimental variables in this study. Taxpayer compliance is a dependent variables in this analysis. taxpayers registered at the Pajajaran I Samsat Office in Bandung City are the population used in this study. The nominal of taxpayers registered in Pajajaran Samsat Office on 2022 is 550,542. The sample determination uses a purposive sample method, with the criteria that taxpayers who have been registered at the Pajajaran Samsat office for at least one year, and taxpayers who have used the e-samsat system. This study relies on primary data collected from a sample of one hundred taxpayers who filled out questionnaires distributed at the Pajajaran Samsat Office in Bandung City. Multiple linear regression is a technique used in the analysis. This research shows that the implementation of tax penalties has a significant and positive impact on taxpayer compliance to pay motor vehicle taxes. Implementation of e-samsat system have a significant and positive impact on taxpayers' compliance to pay motor vehicle tax. Meanwhile, tax waiver has no impact a taxpayers compliance to pay motor vehicle tax